Experiencing Communication Through Youtube Membership: A Phenomenological Study on The Deankt Community - Dimaz Rahmadhi; Tri Widya Budhiharti; Nurkinan Nurkinan (Sean Institute, 2025)
YouTube Membership is a monetization feature that not only provides financial benefits for content creators but also facilitates exclusive communication spaces between creators and audiences. Amid the growing trend of digital participation in Indonesia, it is important to examine how users experience and interpret interactions within such digital communities. This study explores how audiences engage in communication through the YouTube Membership feature, focusing on the DEANKT channel. Using Alfred Schutz’s phenomenological approach, it investigates both the